Use of Antibiotics in Children: A Danish Nationwide Drug Utilization Study. Issue 2 (February 2015) - Pottegård, Anton; Broe, Anne; Aabenhus, Rune; Bjerrum, Lars; Hallas, Jesper; Damkier, Per
Abstract : Background: We aimed to describe the use of systemic antibiotics among children in Denmark. Methods: National data on drug use in Denmark were extracted from the Danish National Prescription Database. We used prescription data for all children in Denmark aged 0 to 11 years from January 1, 2000 to December 31, 2012. Results: We obtained data on 5, 884, 301 prescriptions for systemic antibiotics issued to 1, 206, 107 children. The most used single substances were phenoxymethylpenicillin (45%), amoxicillin (34%) and erythromycin (6%). The highest incidence rate of antibiotic treatment episodes was observed among children younger than 2 at 827 per 1000 children in 2012. Incidence rates were relatively stable throughout the study period. One-year prevalences in 2012 were 485, 363 and 190 per 1000 children among children aged 0–1, 2–4 and 5–11, respectively. A gradual shift from narrow-spectrum penicillin V to the broader-spectrum amoxicillin was found among children younger than 5. The use of macrolides decreased slightly, especially among those aged 0–1. Minor regional differences were noted, with somewhat higher use in the Capital Region. Skewness in use was most notable among those aged 0–1. There was little evidence of heavy users. Conclusion: Prescribing rate of antibiotics to children in Denmark remained stable at a high level from 2000 to 2012. An increase in the use of broad-spectrum beta-lactam penicillin was noted, but otherwise the prescribing pattern adhered well to National guidelines with respect to choice of antibiotics.